Efeito da modificação covalente da superfície de nanotubos de carbono nas propriedades de nanocompósitos preparados com poliuretanas termoplásticas - Diego Satiro da Cruz (2013)
In this work polymer nanocomposites were prepared with multi-walled carbon nanotubes in order to improve the mechanical properties of two commercial thermoplastic polyurethanes (TPUs). Chemical modification of the nanotubes surface (functionalization) was carried out by acid treatment. Those modified MWCNTs with different degrees of functionalization were dispersed in the commercial TPU matrixes by the solution mixing method at different concentrations of MWCNT in order to evaluate its influence on the composite mechanical properties by employing tensile tests. The nanocomposites were also characterized by physicochemical methods on the effort to correlate the obtained structure with the materials properties. The data showed that the dispersion achieved using functionalized nanotubes provided significant improvements in the mechanical properties of the composites compared to the pure polymer. The composites prepared with nanotube/TPU Bayer showed superior mechanical properties in comparison with those observed in the composites prepared with the Huntsman TPU indicating that the interaction nanotube/matrix was more effective on the composites with Bayer TPU. The best results were obtained with nanotubes that present higher degree of functionalization at concentrations ranging from 0.01% to 0.05 wt% MWCNT. The MWCNTs have improved modulus and tensile strength without loss of elongation at break. Gains of 30-40% in mechanical properties, such as those obtained in this study, may boost the demand for commercial application of polymer nanocomposites with MWCNT, especially when small amounts of filler need to be employed.